Advances in industrial and labor relations. vol. 27 - Lewin, David; Gollan, Paul J. (Advances in industrial and labor relations ;, 2023)
Volume 27 of Advances in Industrial and Labor Relations (AILR) contains five peer-reviewed papers highlighting key aspects of employment relations across a variety of disciplinary perspectives. These papers feature historical and legal analyses of work regulation, intra-organizational analysis of employee development and entry-level hiring decisions, prospects for unionization and other forms of collective association in gig economy companies, and analysis of on-line versus in-person mediation of employment disputes involving allegations of discrimination. As with prior AILR volumes, the papers in Volume 27 display a variety of quantitative and qualitative research methods. These range from primary research methods such as case studies, survey, interviews, and historiography to longitudinal and cross-sectional empirical studies and theory building.